Kebijakan Manajemen Keuangan, Nilai Perusahaan dan Kinerja Keuangan Perusahaan pada Perusahaan Manufaktur di Bursa Efek Indonesia - Ninik Nuraeni; Yunike Berry (Jurnal Riset Akuntansi, 2019)
The purpose of this study was to analyze the effect of financial management policies on financial performance and firm value, the effect of financial performance on firm value, and analyze the indirect influence of financial management policies on firm value through financial performance. Financial management policies consist of investment decisions, funding decisions , and dividend policy. The method used is descriptive statistics and path analysis which is a continuation of multiple regression analysis. Data collection techniques are in the form of financial report documentation issued by manufacturing companies in 2014-2016. Meanwhile, the sampling technique uses purposive sampling, with a total sample of 38 companies. Based on the test results it was concluded that investment and funding decisions had a significant effect on financial performance and firm value, while dividend policy did not affect financial or nil performance ai company, financial performance has a significant and negative influence on firm value. For mediation results, it was found that there is an indirect relationship between investment decisions and funding decisions with firm value through financial performance, but financial performance is not a mediation between dividend policy and firm value.